A companion to the Muslim world rulers, rebels, and rogues - Sajoo, Amyn B. (Muslim heritage series, 2009)
This immaculately researched, but at the same time thoroughly accessible, book offers a journey into the full range of experience -- past and present, secular and sacred -- of the peoples and cultures that share in Islamic tradition. A Companion to the Muslim World comprises an attractive and coherent attempt by distinguished scholars to contibute towards that vital process of comprehension.